TINJAUAN KETIDAKLENGKAPAN RESUME MEDIS RAWAT INAP PESERTA JKN (JAMINAN KESEHATAN NASIONAL) GUNA MENUNJANG KUALITAS PENGKLAIMAN DI RSUP Dr. HASAN SADIKIN BANDUNG - ,, Suharto; Hakim, Luqmanul (Jurnal TEDC; Vol 13 No 1 (2019): Jurnal TEDC, 2019)
Based on preliminary study in RSUP Dr. Hasan Sadikin Bandung found incompleteness of medical resume replenishment of additional diagnosis, doctor's name and signature, additional actions and resumes are not in the file so it can impede the process of claim. The purpose of this research is to know the filling of medical resumes in RSUP Dr. Hasan Sadikin Bandung. The method used is a quantitative descriptive method. Samples were taken from the period of October 2019 – December 2019 as many as 255 samples using Sugiyono table calculations. The 3-month medical resume sheet population in RSUP Dr. Hasan Sadikin Bandung is a total of 9,696 files. The data collection techniques used are observation methods, interview methods, literature study methods, and documentation. The results of research conducted by the author at Dr. RSUP Hasan Sadikin Bandung, there were 255 resumes of JKN hospitalized patients examined by the authors who found the highest incompleteness data, namely the Name and Signature of the Doctor as much as 125 or 49%. The highest completeness data is the resume sheet that is in the file and is filled in 223 or 87%. Dr. Hasan Sadikin Hospital does not yet have a standard operating procedure (SPO) regarding the completeness of filling inpatient medical resumes. The incomplete filling of medical resumes will affect the quality of the claim, the delay in the claim process can be detrimental to the hospital. The author recommends that a Standard Operating Procedure (SPO) be made for completing the medical resume and giving warning and sanctions to non-compliant Medical Staff Groups.